Condicionamento fisiológico de sementes de soja, componentes de produção e produtividade - da Silva, Tiago Alexandre [UNESP]; da Silva, Pedro Bento [UNESP]; Da Silva, Edvaldo Aparecido Amaral [UNESP]; Nakagawa, João [UNESP]; Cavariani, Claudio [UNESP] (FapUNIFESP (SciELO), 2016)
The Soybean crop is extremely relevant to the Brazilian economy. Priming is a technique that allows improvement of seed quality, especially those of low vigor. Vigor is defined as the ability of the seed to perform adequately when exposed to different environmental conditions. High vigor seeds generate plants with higher emergency speed and superior yield components, favoring into a higher seed yield. The objective of this work was to evaluate the agronomic behavior of soybean plants under field conditions originated from primed seeds with different level of vigor. Yield components and soybean yield were also evaluated. Seed priming in seed with medium vigor positively influences the components (seedling emergence, first pod height, number pods/plant, number of seeds/plant, number of seeds/ pod) and favored productivity of soybean cultivar ‘M7211RR’. Different levels of vigor of soybean seeds cause differences in the number of pods/plant.
Seed priming, yield components and yield of soybean
Keywords: Deterioration; Priming; Seed vigor